Effect of Clostridium butyricum and Butyrate on Intestinal Barrier Functions: Study of a Rat Model of Severe Acute Pancreatitis With Intra-Abdominal Hypertension - Zhao, Han-bing; Jia, Lin; Yan, Qing-qing; Deng, Qi; Wei, Bo (Frontiers in Physiology, 2020)
Background/Aims Severe acute pancreatitis (SAP) is associated with intra-abdominal hypertension (IAH) and abdominal compartment syndrome (ACS), but treatment of these conditions is difficult. We studied a rat model of SAP + IAH to determine the effect of oral administration of Clostridium butyricum and butyrate (its major metabolite) on intestinal barrier functions. Methods A total of 48 rats were assigned to four groups, with 12 rats per group: Sham, SAP+IAH, SAP+IAH+C. butyricum, and SAP + IAH + butyrate. SAP was induced by sodium taurocholate infusion into the biliopancreatic duct, intra-abdominal pressure (IAP), mortality was measured 24 h later, and then rats were euthanized. The plasma levels of several markers [amylase, diamine oxidase (DAO), fluorescein isothiocyanate (FITC)-dextran, tumor necrosis factor alpha (TNF-α), interleukin (IL)-6, IL-1β, IL-12, lipopolysaccharide (LPS)] and fecal butyric acid level were determined. The pancreas and intestine were examined using histology, and RT-PCR and Western blotting of intestinal tissues were used to measure the expression of six markers {tight junction proteins [zonula occludens protein-1 (ZO-1), claudin-1, claudin-2, occluding], matrix metalloproteinase 9 [MMP9], and TNF-α}. The gut flora of the rats was examined by 16S rRNA sequencing. Results Induction of SAP + IAH altered several functions of the intestinal barrier, and enhanced intestinal permeability, decreased the levels of ZO-1, claudin-1, occludin, the richness and diversity of the microflora community, the relative abundance (RA) of Firmicutes, and the number of probiotic organisms. However, induction of SAP+IAH increased the expression of claudin-2, MMP9, and TNF-α, and the RA of Proteobacteria and pathogens in the feces. Rats that received oral C. butyricum or butyrate had reduced intestinal injury and plasma levels of DAO, LPS, and inflammatory cytokines. Conclusion This study of rats with SAP+IAH indicated that oral dosing of C. butyricum or butyrate reduced intestinal injury, possibly by altering the functions of the intestinal mucosal barrier.